Ensayo sobre la historia de la sociedad civil - Ferguson, Adam, 1723-1816; Wences Simon, María Isabel; Ferguson, Adam, 1723-1816. (Tres Cantos, Madrid, España : Ediciones Akal, S.A., 2012)
Adam Ferguson's Essay on the History of Civil Society (first published in 1767) is a classic of the Scottish - and European - Enlightenment. Drawing on such diverse sources as classical authors and contemporary travel literature, Ferguson offers a complex model of historical advance which challenges both Hume's and Smith's embrace of modernity and the primitivism of Rousseau. Ferguson combines a subtle analysis of the emergence of modern commercial society with a critique of its abandonment of civic and communal virtues. Central to Ferguson's theory of citizenship are the themes of conflict, play, political participation and military valour. The Essay is a bold and novel attempt to reclaim the tradition of active, virtuous citizenship and apply it to the modern state.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed April 29, 2016)
Keywords: Civilization -- History; Civil society -- History; Electronic books